Phytosociology, successional level, and conservation of the woody component in a "restinga" of Maranhão island, Brazil - Vieira Serra, Flávia Cristina; Almeida Jr., Eduardo Bezerra de (Revista de Biología Tropical, 2021)
Introduction: The “restingas” (coast vegetation) can serve as a species corridor in ecotonal environments due to the particulars regarding the composition of the flora. The studies covering the entire length of the Maranhão state coast are necessary to understand the diversity and distribution of plant species present in the “restingas”. Objective: The objective of this study was to characterize the structure and conservation of the woody vegetation of a “restinga” in Maranhão. Methods: Phytosociological sampling of woody vegetation was carried out using the quadrants method, followed by classification of species by successional group; in addition to analyzing the diametric and hypsometric data of the populations whose species presented the highest importance value (IV). Results: In total, 24 species and 16 families were identified, 72 % of which were classified in the initial stages of succession. The values of H’ and J’ were 2.637 nat.ind-1and 0.830, respectively. The mean height and diameter were 2.1 m and 27.66 cm, respectively. The species Coccoloba ramosissima Wedd., Byrsonima crassifolia (L.) Kunth, Anacardium occidentale L., Manilkara triflora (Allemão) Monach, and Astrocaryum vulgare Mart. presented the highest IVs. Conclusions: It was observed that characteristics such as size, power of regrowth, and ease of regeneration processes could be useful for choosing target species for recovery actions in coastal areas.